Circularly Polarized Leaky-Wave Antenna Based on Low-Loss Transmission Line - Xingying Huo; Zheng Li (International Journal of Antennas and Propagation)
A leaky-wave antenna with circular polarization property is proposed in millimeter-wave band, which can be applied in the wireless communication systems and remote sensing. The radiation is produced by the periodic patches on both sides of the dielectric slab of the antenna based on a low-loss planar Goubau line structure. The circular polarization unit cell of this antenna is made of two pairs of H-shaped patches, orthogonally set on each side of the dielectric substrate, which can efficiently reduce the cross polarization. This antenna is excited by a central strip line on the upper surface of the slab, removing the ground of the traditional microstrip structure, to reduce the loss of the antenna. The circular polarization property is achieved by optimizing the size and the distribution of the radiation unit cell and the structural periodicity. The radiation performance of this antenna is analyzed by CST simulation, which shows that the overlapping bandwidth of this antenna for 3 dB axial ratio with S11 < −10 dB is about 5.3%, with cross polarization 23 dB lower than copolarization. The simulated maximum directivity is l5.5 dBi with efficiency over 90% during the whole band.